Análise da dinâmica da perda de solo no município de Rio Verde-GO entre 1985 e 2022 - Fabrício, Lorrane Vicente (2025)
This study aimed to analyze the relationship between agricultural expansion and soil erosion dynamics in the municipality of Rio Verde, Goiás, during the years 1985, 2005, and 2022. The adopted approach was based on an integrated analysis of the physical environment. In this context, an effort was made to correlate natural and anthropogenic factors in order to understand how these elements influence the emergence of erosive processes in the municipality. To estimate soil loss rates due to sheet erosion, the widely used mathematical model known as the Universal Soil Loss Equation (USLE) was applied. For the analysis and mapping of linear erosion processes, the visual inspection method was employed using high-resolution satellite imagery. The results regarding the natural characteristics of the R, K, and LS factors revealed a high rainfall erosivity potential in the region, concentrated between the months of November and March. Soil erodibility ranged from very low to very high, with over 22.16% of the area showing very low or low levels, 72.32% classified as medium, and 5.01% as high or very high. Concerning the topographic factor, 92.46% of the area corresponded to low LS values, 6.27% to the moderate class, and only 1.27% to areas classified as high to very high. In terms of the anthropogenic variable represented by the CP factor, one of the most significant changes was the conversion of pasture areas into predominantly agricultural land. In 1985, pasture covered 36.02% of the area, while agriculture accounted for 15.89%. By 2022, pasture areas had decreased to 11.28%, whereas agricultural activities had expanded to 55.68% of the total area. After overlaying the USLE factors, three distinct results were obtained regarding estimated soil loss. A progressive increase in the medium soil loss class was observed, to the detriment of the null to moderate class. The CP factor (agriculture) proved to be one of the main drivers behind the increase in medium soil loss, as less susceptible areas were gradually converted into predominantly agricultural land over the past 37 years—areas which, under the same conditions, exhibited greater susceptibility to soil loss. Furthermore, the highest soil losses occurred in areas with elevated R, K, and LS factor values and were intensified by the CP factor (pasture). This pattern was especially evident in the southwestern region of the municipality, where the interaction between natural and anthropogenic factors significantly influences soil loss. In addition, several erosive features at different stages of development were identified, mainly associated with pasture areas that lack proper management. These areas, ranging from flat to strongly undulating relief, are predominantly composed of Dystrophic Red Latosols and Dystrophic Litholic Neosols, which exhibit medium and very high erodibility, respectively.